Performance Appraisal: Decisions, Feedback and Future Developments - Siti Mariam, Abdullah; Rusli, Ahmad; Nur Fatihah, Abdullah Bandar; Ahmad Sofian, Shminan; Helmi, Sumilan (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Employee performance appraisal is a consistent subject of great interest in any organisation. A quick online query will return hundreds of millions sources of information. It adds to the interest when all employees, from top management to the lowest paid have a personal stake in the working of the performance appraisal system as they are all evaluated by others and most of them evaluate others, if not all as in 360-degree performance appraisal. Hence the research project entitled Performance Appraisal: Decisions, Feedback and Future Developments is an effort of a small team of researchers to explore and obtain more insights into the far-reaching subject of performance appraisal (PA), in general and the performance appraisal system, currently utilised in public universities in Malaysia, specifically. The outcomes of the research study will provide a better understanding of the current PA system and the general acceptance from those directly involved in the system, to all major stakeholders in higher education: policy makers in the Ministry of Higher Education, top management in public universities, evaluators and evaluatees with direct experience as `end-users’ of the system, leading to a more efficient and effective decision making in the conduct of performance appraisal. The population for this study consists of all the lecturers in three public universities in East Malaysia: Universiti Teknologi MARA (UiTM), Universiti Malaysia Sabah (UMS) and Universiti Malaysia Sarawak (UNIMAS), numbering about 2,000 academic staff members in total. Employing mainly a survey approach, a bilingual questionnaire was designed to be administered on a drop-pick arrangement with the universities and an online survey form to reach more respondents. Additional information to substantiate the findings from the survey will be obtained through several focused interview groups, selected from the sampling. Currently, the research is in the pilot testing stage. A pilot study was conducted among lecturers in UNIMAS to get initial feedback on the instrument design and to test the validity, reliability and administrability of the questionnaire. The pilot study results is in the process of analysis and will be used for further revision of the instrument and the research procedure, if necessary. Once completed, the survey will be conducted in the three public universities and the findings are expected to be finalised around mid 2019. Interestingly, one of the tangible outcomes of this research study is the Performance Appraisal Intervention Kit (PAI-KIT). PAI-KIT consists of the SWOT instrument (resembling the survey questionnaire which can be tailored to the needs and the current performance appraisal system in a particular organisation), data analysis and evaluation report as well recommendations for intervention. Thus PAI-KIT is a complete intervention strategy to address the issues or to prevent issues, as the case may be, in each organisation based on its context. Besides, it is collaboration between academics and interested organisations to contribute what we do best; both theory and practice. The proposal of PAI-KIT was given a merit mention during InTEX18 Expo held concurrently with InTEX conference organised by UNIMAS in Pullman Hotel, Kuching last year.